Tonal Targets in Early Child English, Spanish, and Catalan. (June 2013) - Astruc, Lluïsa; Payne, Elinor; Post, Brechtje; Vanrell, Maria del Mar; Prieto, Pilar
This study analyses the scaling and alignment of low and high intonational targets in the speech of 27 children – nine English-speaking, nine Catalan-speaking and nine Spanish-speaking – between the ages of two and six years. We compared the intonational patterns of words controlled for number of syllables and stress position in the child speech to the adult target speech provided by their mothers, and to a dataset of adult-directed speech recorded at a later stage for the purpose of measuring pitch height. A corpus of 624 utterances was elicited using a controlled naming task and analysed within the Autosegmental Metrical framework. Measuring the pitch height and pitch timing of nuclear pitch accents, we found that once the effects of syllable duration are accounted for, young children reach tonal targets with remarkable precision. Overall, the results indicate that the phonetic aspects of intonation are acquired from a very early age. Even the youngest children show adult-like alignment of the low target, although mastery of the high target increases with age. Young Spanish-speaking children, however, show a more precise attainment of pitch scaling and alignment of their (high) tonal targets than do Catalan and English children; where the ambient language lies within a general prosodic typology appears to influence the acquisition of tonal targets.